Emotional Picture Perception: Repetition Effects in Free-Viewing and during an Explicit Categorization Task - Mastria, Serena; Ferrari, Vera; Codispoti, Maurizio (Frontiers in Psychology, 2017)
Several studies have found that, despite a decrease in the overall amplitude of the late positive potential (LPP) with repeated presentation of the same picture, emotional stimuli continue to elicit a larger late positive potential than neutral ones. These findings seem to support the hypothesis that the affective modulation of the LPP reflects a mandatory process and does not rely on stimulus novelty. However, in these studies participants were asked to merely look at the pictures, without carrying out any additional task (free-viewing), making picture emotionality the most salient aspect of the stimulus, despite its repetition. The current study aimed to examine the impact of an explicit categorization task on the emotional processing of repeated pictures. To this purpose, ERPs to novel and repeated pictures were measured during free-viewing as well as during an explicit categorization task, where the emotional content of the pictures was task-irrelevant. The within-subject comparison between the free-viewing and task context revealed that the overall LPP habituated more rapidly in the free-viewing condition, but, more importantly, the LPP affective modulation was unaffected by task requirements during both novel and repeated presentations. These results suggest that the affective modulation of the LPP reﬂects an automatic engagement of cortico-limbic motivational systems, which continues to take place regardless of stimulus novelty and task context.